2021
DOI: 10.21776/ub.jrm.2021.012.02.15
|View full text |Cite
|
Sign up to set email alerts
|

Meshing Strategi untuk Memprediksi Hambatan Total pada Kapal Planing Hull

Abstract: A high-speed vessel has a range of Froude Number (Fr) > 1. A drag prediction method based on Fr > 1 has high complexity because it is influenced by trim and heave motions. Hence, a specific treatment is necessary to obtain accurate results. This study is using mesh density and mesh shapes to predict the total drag of a planing hull ship. The Computational Fluid Dynamic (CFD) results show good performance in predicting the drag, trim, and heave. Mesh density of 2300K shows the most stabilized result. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Moreover, the k-epsilon model is suitable for the application with a high Reynold number; in this case, the Reynolds number was 6.8 x 10 6 . Subsequently, k-epsilon is more accurate in modelling the complex flow detachment; thereby, this model would provide precise results to predict the drag coefficient on the car's body [34]. In the simulation, the truck geometry was symmetrical, assuming that both sides had the same flow pattern.…”
Section: Domain and Boundary Conditionsmentioning
confidence: 99%
“…Moreover, the k-epsilon model is suitable for the application with a high Reynold number; in this case, the Reynolds number was 6.8 x 10 6 . Subsequently, k-epsilon is more accurate in modelling the complex flow detachment; thereby, this model would provide precise results to predict the drag coefficient on the car's body [34]. In the simulation, the truck geometry was symmetrical, assuming that both sides had the same flow pattern.…”
Section: Domain and Boundary Conditionsmentioning
confidence: 99%
“…Penentuan hambatan dengan menggunakan metode CFD yaitu karena lambung katamaran memiliki bentuk lambung yang lebih kompleks dibandingkan dengan lambung monohull. Hasil simulasi CFD dapat diterima dengan rumus empiris menghasilkan error di bawah 5% [3]. Dengan nilai error yang relatif kecil, kesalahan dalam pemilihan mesin dapat diminimalisir.…”
Section: Pendahuluanunclassified
“…Previous research has studied mesh independency by using the same ship model [6]. Within those research, mesh independency characteristics are studied using five grid variations consisting of 0.48 M, 0.89 M, 1.44 M, 2.33 M, and 2.99 M, as shown in Figure 6.…”
Section: Validation and Benchmarkmentioning
confidence: 99%
“…This research was then broadly used by researchers worldwide to perform numerical computational verifications. Studies on the mesh density of the Fridsma hull have been reported to ensure accurate results [6]. Recent research on Fridsma hull is concerned with hull modification.…”
Section: Introductionmentioning
confidence: 99%